The Use of Songs in Teaching Online Listerning Class : A Descriptive Qualitative Research - Pratiwi Rahayu; Diana Paskalisa; Rini Al Baqoroh (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
This study aims to find out the use of songs as a media in teaching listening skill in the online classroom. The descriptive qualitative research design was conducted in grade seven of middle school which involved 23 students as the participants. This study used three types of data collection techniques including observation, questionnaire and interview. The results of data analysis show that by using songs in online listening class could facilitate the students in improving their listening skill, especially in improving their vocabulary and pronunciation. Furthermore, the results of the interview show that the students feel enjoy while studying through songs. The students agreed that the use of songs in online class can help them to improve their listening skill. Due to the limitation of the study, it is recommended for every teacher who wants to use songs in online class to fully select the appropriate songs for students. Despite the need for further study, songs can be used as a media in teaching online listening class to EFL learners.